2012
DOI: 10.1074/jbc.m112.362327
|View full text |Cite
|
Sign up to set email alerts
|

Polyalanine-independent Conformational Conversion of Nuclear Poly(A)-binding Protein 1 (PABPN1)

Abstract: Background: Mutations in the gene of the nuclear polyadenylate-binding protein 1 (PABPN1) lead to oculopharyngeal muscular dystrophy (OPMD) and aggregation of PABPN1. Results: Fibrillar structures occur independently of the OPMD causing mutation. Conclusion: OPMD might be caused by processes other than fibrillation. Significance: Fibrils of full-length PABPN1 have been obtained which might have structures identical to those found in OPMD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…Purified fragments of the N-terminal domain of PABPN1 carrying an expanded stretch of 17 alanines show a greater propensity to form fibrils that are more resistant to solubilization than fragments with 10 alanines [59]. However, subsequent work using full-length PAB-PN1 revealed that fibril formation is independent of the alanine tract and that the C-terminal domain confers aggregation [60] as both the wild-type and alanine-expanded PABPN1 proteins could form aggregates and removing the N-terminal stretch of alanines did not prevent aggregation [60]. Thus, these in vitro studies do not support a model where alanineexpanded PABPN1 is more prone to aggregation, at least in vitro, than the wild-type protein.…”
Section: Approaches Used To Study the Effects Of Mutant Pabpn1mentioning
confidence: 99%
“…Purified fragments of the N-terminal domain of PABPN1 carrying an expanded stretch of 17 alanines show a greater propensity to form fibrils that are more resistant to solubilization than fragments with 10 alanines [59]. However, subsequent work using full-length PAB-PN1 revealed that fibril formation is independent of the alanine tract and that the C-terminal domain confers aggregation [60] as both the wild-type and alanine-expanded PABPN1 proteins could form aggregates and removing the N-terminal stretch of alanines did not prevent aggregation [60]. Thus, these in vitro studies do not support a model where alanineexpanded PABPN1 is more prone to aggregation, at least in vitro, than the wild-type protein.…”
Section: Approaches Used To Study the Effects Of Mutant Pabpn1mentioning
confidence: 99%
“…Interactions of the poly-Ala stretch with functional domain of the protein may also trigger pathological behavior of PABPN1. But before concluding this type of remarks, further conformational study with the whole N-terminal domain and protein PABPN1 in native as well as mutant form should be considered as Winter et al report poly-Ala independent aggregation of PABPN1 protein [35]. The helix adopting character of poly-Ala stretch and its relation to pathological mechanism by mutant PABPN1 will be published in our forthcoming publication.…”
Section: Discussionmentioning
confidence: 93%
“…Solid-state NMR studies identified a rigid fibrillar core that contained the alanine segment (Sackewitz et al, 2008a). Unexpectedly, fibril formation of the fulllength protein was not alanine-dependent (Winter et al, 2012). Furthermore, fibrils formed by full-length PABPN1 did not exhibit the high resistance against solubilizing agents as those of the N-terminal domain, and it became evident that fibrils from the N-terminal domain and fulllength PABPN1 do not share any common features.…”
Section: The Link Between Alanine Extensions and Protein Function Or mentioning
confidence: 97%
“…It is so far unclear why fibril formation alaninedependent in the case of the N-terminal domain but not in the context of full-length PABPN1 (Winter et al, 2012). Alanine peptides have been called conformational chameleons because they display the whole spectrum, from high to low α-helicities, depending on the flanking residues (Miller et al, 2001).…”
Section: The Link Between Alanine Extensions and Protein Function Or mentioning
confidence: 99%